Internal-doped waterproof material for autoclaved aerated concrete and preparation method of internal-doped waterproof material
By modifying calcium stearate to synergistically interact with graphite materials, and adding silica fume and aerated concrete waste, the problem of insufficient water absorption and durability of autoclaved aerated concrete is solved, and higher water resistance and mechanics are achieved performance.
Patent Information
- Application Number
- CN202411509505.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-10-28
AI Technical Summary
Due to the high porosity and large surface free energy, autoclaved aerated concrete will reduce its strength and insulation properties after water absorption, and its frost resistance and durability will be deteriorated. It is difficult for existing waterproofing agents to take into account the fluidity and gas generation resistance of the slurry.
Calcium stearate modified calcium carbonate works synergistically with soil-like graphite and fine scale expanded graphite, and combined with a certain amount of silica fume and aerated concrete waste, C-S-H gel and tobyl mullite crystals are generated to improve the flow of the slurry and reduce air resistance.
It significantly improves the water resistance and durability of autoclaved aerated concrete, enhances the fineness and uniformity of the pore size of the blank, reduces the landslide of the blank, and ensures the cutting strength and mechanical properties of the product.
Smart Images

Figure BDA0005105043090000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of wall materials, and in particular to an internally mixed waterproof material for autoclaved aerated concrete and a preparation method thereof. Background Art
[0002] Autoclaved aerated concrete has the advantages of a wide range of raw material sources, capital saving, waste recycling, and low transportation costs. However, autoclaved aerated concrete has a high porosity and a large surface free energy. It often absorbs water, which leads to a decrease in its strength and thermal insulation performance, and a deterioration in its frost resistance and durability. After the product absorbs water, it is very easy to cause large shrinkage during drying, and the bonding strength with the plastering mortar decreases during construction, causing problems such as wall hollowing, mold, cracking, and large-scale shedding, which affects the beauty of the building wall and shortens its service life.
[0003] At present, the main ways to waterproof autoclaved aerated concrete are matrix structure optimization and modification using waterproofing agents. Matrix structure optimization is to improve the waterproof performance of the product by adjusting the material formula and process parameters to improve the pore structure of concrete and the crystal-gel ratio of the pore wall. Reducing the water-to-material ratio is a common method. Low water-to-material ratio is conducive to reducing the water absorption performance of aerated concrete. However, in practical applications, the improvement effect is limited. At the same time, it may affect the stability of casting, the structure of pores and the thickening and hardening speed of the blank, which may easily cause unstable product quality or even unqualified product quality. The application method of waterproofing agent in aerated concrete is usually surface coating or internal modification. The surface-coated waterproofing agent loses its waterproofing effect after the surface is damaged, while the internally added waterproofing agent still has a waterproofing effect after the surface is worn during transportation. Commonly used organic waterproofing agents include silicone waterproofing agents, fatty acid salt waterproofing agents, paraffin emulsion waterproofing agents and water-based crystalline waterproofing agents, and inorganic waterproofing agents include chlorides, inorganic aluminates and zirconium compounds. These waterproofing agents will have better effects when used in concrete. However, aerated concrete is different from ordinary concrete. The static and curing processes are the key to ensuring the quality of aerated concrete. Ordinary waterproofing agents will affect the gasification, thickening and hardening of the slurry during the static process, the autoclave curing process, or cause problems such as uneven pore structure, unqualified bulk density, long static time, or long steam curing time.
[0004] Patent CN105036677A discloses a kind of autoclaved aerated concrete block or plate and preparation method, in which chloride, organosilicon waterproofing agent, water reducing agent and calcined gypsum are added to reduce the water absorption rate of the block and improve durability. However, after pouring, the gasification process of aluminum powder in aerated concrete production is slow, generally lasting 10-30min, and the addition of water reducing agent reduces the water-to-material ratio, while chloride accelerates the hydration of C3A in cement, and calcium hydroxide formed by chloride and cement hydration generates calcium chlorate that is not easily soluble in water, reducing the alkalinity of the slurry. In addition, calcined gypsum and fly ash in the ingredients generate part of calcium sulfate, and the viscosity of the slurry increases significantly. Under this environment, aluminum powder reacts slowly in an alkaline environment, and the gasification resistance increases at the same time, which may eventually cause gasification to be blocked and the gasification height is not high enough, and the height of the blank is difficult to meet the technical requirements of cutting, not to mention that the bulk density is greatly increased. Therefore, solving the compatibility of waterproofing agent with aerated concrete raw materials and bubbles becomes a problem that needs to be studied urgently.
[0005] At present, ultrafine particles have been used to fill the internal pores of aerated concrete to improve mechanical properties and durability, such as nano calcium carbonate. However, nano calcium carbonate particles are small and easy to agglomerate, which makes it easy to cause the slurry to have a high consistency and large gas resistance in actual application. Although the strength is improved, the bulk density is also increased. Using calcium stearate to modify light calcium carbonate can improve its agglomeration. At the same time, calcium stearate can improve the foaming of aerated concrete slurry, making the pore size of the body fine and uniform, and reducing body collapse; the lubricity of earthy graphite powder itself can improve the fluidity of the slurry, and filling it into pores and micro cracks can also increase the mechanical properties; fine scale expanded graphite has a loose porous structure and is easy to form a hydrophobic structure.
[0006] The invention utilizes calcium stearate to modify calcium carbonate, and the modified calcium carbonate has a synergistic effect with earthy graphite and fine flake expanded graphite, so that the hydrophobicity is stronger; a certain amount of silica fume and aerated concrete waste are added to improve the fluidity of the slurry and reduce the gas generation resistance; the amorphous silicon and ultrafine powder react with Ca(OH)2 to generate CSH gel, so that the calcium-silicon ratio in the green body is reduced, and the cutting strength of the green body is guaranteed; the silica fume with fine particles is more likely to react to generate tobermorite crystals during the steaming process, and provides a crystal guiding effect, so that the internal mineral structure of the aerated concrete is better and the mechanical property is higher. Summary of the invention
[0007] The purpose of the present invention is to provide an internal waterproof material for autoclaved aerated concrete and a preparation method thereof, so as to solve the technical problems of high water absorption and poor durability of aerated concrete.
[0008] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0009] An internally admixed waterproof material for autoclaved aerated concrete comprises a mixture A and a mixture B in a mass ratio of 1:4, and a dispersant less than 0.5wt% of the total mass of the mixture A and the mixture B; the mixture A comprises the following components in mass ratio: 5wt% of fine flake expanded graphite, 5-10wt% of earthy graphite, and 85-90wt% of aerated concrete waste; the mixture B comprises the following components in mass ratio: 80-85wt% of modified light calcium carbonate, 10-15wt% of quicklime, and 5wt% of silicon powder.
[0010] Furthermore, the fine flake expanded graphite is obtained by oxidation, acidification intercalation, and high-temperature calcination of fine flake graphite with a particle size of 0.075 to 0.1 mm;
[0011] Preferably, the fine scale expanded graphite is oxidized and acidified by potassium permanganate, perchloric acid, glacial acetic acid and nitric acid. 细鳞片石墨 ∶m 高锰酸钾 :V 高氯酸 :V 冰乙酸 :V 硝酸 =5g:1.7g:10mL:3.5mL:3mL, the reaction environment temperature is 40°C, the reaction time is 30min, and then the fine flake expanded graphite is obtained at a high temperature of 600°C, and the expansion volume of the fine flake expanded graphite is 190mL / g.
[0012] Furthermore, the aerated concrete waste is one or more of sand aerated concrete waste, fly ash aerated concrete waste, and slag aerated concrete waste;
[0013] Preferably, the aerated concrete waste is of the same type as the autoclaved aerated concrete, that is, if the autoclaved aerated concrete is fly ash aerated concrete, the aerated concrete waste used should be fly ash aerated concrete waste, which can prevent the color of the aerated concrete product and the proportion of the steam-cured product from being changed.
[0014] Furthermore, the water content of the aerated concrete waste is not higher than 2wt%; the aerated concrete waste is obtained by crushing aerated concrete blocks, and the particle size of the aerated concrete waste is 1 to 5mm.
[0015] Furthermore, the carbon content of the earthy graphite is ≥95wt% and the particle size is 0-0.045μm.
[0016] Furthermore, the modified light calcium carbonate is obtained by modifying calcium carbonate, and the specific operation is as follows: light calcium carbonate and calcium stearate are weighed in a mass ratio of 1:0.015 and mixed evenly, and then ground by vibration mill for 2 to 5 minutes to obtain modified light calcium carbonate.
[0017] Furthermore, the CaO content of the quicklime is ≥80wt%, and the particle size is 10-30mm.
[0018] Furthermore, the silicon ash is a byproduct of smelting ferrosilicon alloy or silicon metal in an electric arc furnace, and the SiO2 content is ≥90wt%.
[0019] Furthermore, the dispersant is a cement grinding aid.
[0020] The invention utilizes calcium stearate to modify calcium carbonate to obtain modified light calcium carbonate. The modified light calcium carbonate, earthy graphite and fine flake expanded graphite act synergistically to enhance hydrophobicity. A certain amount of silica fume and aerated concrete waste are added to improve the fluidity of the slurry and reduce the gas generation resistance. The amorphous silicon and ultrafine powder react with Ca(OH)2 to generate CSH gel, so that the calcium-silicon ratio in the green body is reduced and the cutting strength of the green body is ensured. The fine silica fume is more likely to react to generate tobermorite crystals during the steaming process, providing a crystal guiding effect, so that the internal mineral structure of the aerated concrete is better and the mechanical properties are higher.
[0021] The present invention also provides a method for preparing an internally-added waterproof material for autoclaved aerated concrete, comprising the following steps:
[0022] S1. Weigh fine flake expanded graphite, earthy graphite and aerated concrete waste according to mass ratio, grind and mix them evenly to obtain mixture A;
[0023] S2. Weigh modified light calcium carbonate, quicklime and silica fume according to the mass ratio, grind and mix them evenly to obtain a mixture B;
[0024] S3. Weigh mixture A and mixture B in a mass ratio of 1:4, add a dispersant in an amount less than 0.5wt% of the total mass of mixture A and mixture B, grind and mix until the residue on a 45μm sieve is ≤8%, and obtain an internally mixed waterproof material.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] 1. The waterproof material of the present invention has good compatibility with the raw materials and bubbles of autoclaved aerated concrete. Calcium stearate can improve the foaming of aerated concrete slurry, make the pore size of the green body fine and uniform, reduce the collapse of the green body, and have little effect on the batching scheme, process conditions, casting stability, and product quality.
[0027] 2. The waterproof material of the present invention is applied in autoclaved aerated concrete. Modified light calcium carbonate and silica powder can be filled into the aerated concrete structure to improve the overall strength. Modified nano calcium carbonate cooperates with earthy graphite and fine flake expanded graphite to easily form a hydrophobic layer, which can reduce the water absorption rate of the product and improve the durability of aerated concrete. The waterproof material is internally modified, so there is no need to worry about the block affecting the water absorption of the material after surface wear. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0029] Example 1
[0030] As a preferred embodiment of the present invention, an internally-admixed waterproof material for autoclaved aerated concrete disclosed in this embodiment includes a mixture A and a mixture B in a mass ratio of 1:4, and a dispersant accounting for 0.1wt% of the total mass of the mixture A and the mixture B.
[0031] The mixture A comprises the following components in mass ratio: 5wt% of fine flake expanded graphite, 10wt% of earthy graphite, and 85wt% of aerated concrete waste; the mixture B comprises the following components in mass ratio: 85wt% of modified light calcium carbonate, 10wt% of quicklime, and 5wt% of silicon powder.
[0032] In this embodiment, the preparation method of the internally mixed waterproof material for autoclaved aerated concrete comprises the following steps:
[0033] S1, weighing 5wt% of fine flake expanded graphite, 5wt% of earthy graphite and 90wt% of aerated concrete waste, grinding and mixing them uniformly to obtain a mixture A;
[0034] S2, weighing 80wt% of modified light calcium carbonate, 15wt% of quicklime and 5wt% of silica fume, grinding and mixing them uniformly to obtain a mixture B;
[0035] S3. Weigh mixture A and mixture B in a mass ratio of 1:4, add 0.1wt% of dispersant (triethanolamine) to the total mass of mixture A and mixture B, grind and mix until the residue on a 45μm sieve is ≤8%, and obtain an internally mixed waterproof material.
[0036] In this embodiment, the fine flake expanded graphite is obtained by oxidizing, acidifying, intercalating, and high-temperature calcining fine flake graphite with a particle size of 0.075 to 0.1 mm.
[0037] In this embodiment, the water content of the aerated concrete waste is 1.5wt% and the particle size is 1-5mm.
[0038] In this embodiment, the aerated concrete waste is sand aerated concrete waste.
[0039] In this embodiment, the carbon content of the earthy graphite is 95wt% and the particle size is 0-0.045μm.
[0040] In this embodiment, the modified light calcium carbonate is prepared by modifying calcium carbonate, and the specific operation is as follows: light calcium carbonate and calcium stearate are weighed in a mass ratio of 1:0.015, mixed evenly, and then vibrated and ground for 5 minutes to obtain modified light calcium carbonate.
[0041] In this embodiment, the CaO content of the quicklime is 82wt% and the particle size is 10-30mm.
[0042] In this embodiment, the silicon ash is a byproduct of smelting ferrosilicon alloy or silicon metal in an electric arc furnace, and the SiO2 content is 93wt%.
[0043] Example 2
[0044] As a preferred embodiment of the present invention, an internally-admixed waterproof material for autoclaved aerated concrete disclosed in this embodiment includes a mixture A and a mixture B in a mass ratio of 1:4, and a dispersant accounting for 0.1wt% of the total mass of the mixture A and the mixture B.
[0045] The mixture A comprises the following components in mass ratio: 5wt% of fine flake expanded graphite, 5wt% of earthy graphite, and 90wt% of aerated concrete waste; the mixture B comprises the following components in mass ratio: 80wt% of modified light calcium carbonate, 15wt% of quicklime, and 5wt% of silicon powder.
[0046] In this embodiment, the preparation method of the internally mixed waterproof material for autoclaved aerated concrete comprises the following steps:
[0047] S1, weighing 5wt% of fine flake expanded graphite, 10wt% of earthy graphite and 85wt% of aerated concrete waste, grinding and mixing them uniformly to obtain a mixture A;
[0048] S2, weighing 85wt% of modified light calcium carbonate, 10wt% of quicklime and 5wt% of silica fume, grinding and mixing them uniformly to obtain a mixture B;
[0049] S3. Weigh mixture A and mixture B in a mass ratio of 1:4, add 0.1wt% of dispersant (triethanolamine) to the total mass of mixture A and mixture B, grind and mix until the residue on a 45μm sieve is ≤8%, and obtain an internally mixed waterproof material.
[0050] In this embodiment, the fine flake expanded graphite is obtained by oxidizing, acidifying, intercalating, and high-temperature calcining fine flake graphite with a particle size of 0.075 to 0.1 mm.
[0051] In this embodiment, the water content of the aerated concrete waste is 1.5wt% and the particle size is 1-5mm.
[0052] In this embodiment, the aerated concrete waste is sand aerated concrete waste.
[0053] In this embodiment, the carbon content of the earthy graphite is 95wt% and the particle size is 0-0.045μm.
[0054] In this embodiment, the modified light calcium carbonate is prepared by modifying calcium carbonate, and the specific operation is as follows: light calcium carbonate and calcium stearate are weighed in a mass ratio of 1:0.015, mixed evenly, and then vibrated and ground for 5 minutes to obtain modified light calcium carbonate.
[0055] In this embodiment, the CaO content of the quicklime is 82wt% and the particle size is 10-30mm.
[0056] In this embodiment, the silicon ash is a byproduct of smelting ferrosilicon alloy or silicon metal in an electric arc furnace, and the SiO2 content is 93wt%.
[0057] Example 3
[0058] As a preferred embodiment of the present invention, an internally-admixed waterproof material for autoclaved aerated concrete disclosed in this embodiment includes a mixture A and a mixture B in a mass ratio of 1:4, and a dispersant accounting for 0.1wt% of the total mass of the mixture A and the mixture B.
[0059] The mixture A comprises the following components in mass ratio: 5wt% of fine flake expanded graphite, 5wt% of earthy graphite, and 90wt% of aerated concrete waste; the mixture B comprises the following components in mass ratio: 80wt% of modified light calcium carbonate, 15wt% of quicklime, and 5wt% of silicon powder.
[0060] In this embodiment, the preparation method of the internally mixed waterproof material for autoclaved aerated concrete comprises the following steps:
[0061] S1, weighing 5wt% of fine flake expanded graphite, 8wt% of earthy graphite and 87wt% of aerated concrete waste, grinding and mixing them uniformly to obtain a mixture A;
[0062] S2, weighing 82wt% of modified light calcium carbonate, 13wt% of quicklime and 5wt% of silica fume, grinding and mixing them uniformly to obtain a mixture B;
[0063] S3. Weigh mixture A and mixture B in a mass ratio of 1:4, add 0.05wt% of dispersant (triethanolamine) to the total mass of mixture A and mixture B, grind and mix until the residue on a 45μm sieve is ≤8%, and obtain an internally mixed waterproof material.
[0064] In this embodiment, the fine flake expanded graphite is obtained by oxidizing, acidifying, intercalating, and high-temperature calcining fine flake graphite with a particle size of 0.075 to 0.1 mm.
[0065] In this embodiment, the water content of the aerated concrete waste is 1.5wt% and the particle size is 1-5mm.
[0066] In this embodiment, the aerated concrete waste is fly ash aerated concrete block waste.
[0067] In this embodiment, the carbon content of the earthy graphite is 95wt% and the particle size is 0-0.045μm.
[0068] In this embodiment, the modified light calcium carbonate is prepared by modifying calcium carbonate, and the specific operation is as follows: light calcium carbonate and calcium stearate are weighed in a mass ratio of 1:0.015, mixed evenly, and then vibrated and ground for 5 minutes to obtain modified light calcium carbonate.
[0069] In this embodiment, the CaO content of the quicklime is 82wt% and the particle size is 10-30mm.
[0070] In this embodiment, the silicon ash is a byproduct of smelting ferrosilicon alloy or silicon metal in an electric arc furnace, and the SiO2 content is 93wt%.
[0071] The internally mixed waterproof material prepared in Example 1 was added to the ingredients of the sand aerated concrete block according to 0.3% of the dry material mass of the raw materials of the autoclaved aerated concrete, and the aerated concrete block 1 was obtained by stirring, pouring, statically stopping, steaming and cutting.
[0072] Take the internally mixed waterproof material prepared in Example 2, add it to the ingredients of the sand aerated concrete block according to 0.5% of the dry material mass of the raw materials of the autoclaved aerated concrete, and mix, pour, stop, steam and cut to obtain the aerated concrete block 2.
[0073] Take the internally mixed waterproof material prepared in Example 3, add it to the ingredients of fly ash concrete blocks according to 0.5% of the dry material mass of the raw materials of autoclaved aerated concrete, and mix, pour, stop, steam and cut to obtain aerated concrete blocks 3.
[0074] Comparative Example 1
[0075] Without adding any waterproof material, the aerated concrete block 4 is obtained by mixing, pouring, stopping, steaming and cutting according to the ingredients of the cement-quicklime-sand aerated concrete block.
[0076] Comparative Example 2
[0077] Without adding any waterproof material, the aerated concrete block 5 is obtained by mixing, pouring, stopping, steaming and cutting according to the ingredients of the cement-quicklime-fly ash aerated concrete block.
[0078] According to GB 11969-2020, aerated concrete blocks 1 to 5 were tested for compressive strength, water absorption, drying shrinkage and frost resistance. The water absorption test was to detect the saturated water absorption for 72 hours. The test results are shown in Table 1.
[0079] Table 1 Test results of mechanical properties and durability of blocks
[0080]
[0081] According to Table 1, the mechanical properties and frost resistance of the control group without the waterproof material of the present invention are poor, and the 72h saturated water absorption rate and drying shrinkage value are high, which are on the edge of qualification; the mechanical properties of the experimental group with the waterproof material of the present invention are significantly improved, the 72h saturated water absorption rate is reduced, and the drying shrinkage value and frost resistance are improved with the reduction of the saturated water absorption rate, which shows that the waterproof material of the present invention improves the performance of the building blocks.
[0082] Finally, it should be noted that the above embodiments are only preferred embodiments of the present invention to illustrate the technical solutions of the present invention, rather than limiting them, and certainly not limiting the patent scope of the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. In other words, any changes or modifications made to the main design concept and spirit of the present invention that have no substantive significance, and the technical problems they solve are still consistent with the present invention, should be included in the protection scope of the present invention. In addition, the direct or indirect application of the technical solutions of the present invention in other related technical fields is also included in the patent protection scope of the present invention.
Claims
1. A waterproof material for autoclaved aerated concrete, characterized in that: The invention comprises a mixture A and a mixture B in a mass ratio of 1:4, and a dispersant in an amount less than 0.5wt% of the total mass of the mixture A and the mixture B; the mixture A comprises the following components in mass ratio: 5wt% of fine flake expanded graphite, 5-10wt% of earthy graphite, and 85-90wt% of aerated concrete waste; the mixture B comprises the following components in mass ratio: 80-85wt% of modified light calcium carbonate, 10-15wt% of quicklime, and 5wt% of silicon powder.
2. The internal waterproof material for autoclaved aerated concrete according to claim 1, characterized in that: The fine flake expanded graphite is obtained by oxidation, acidification intercalation and high temperature calcination of fine flake graphite with a particle size of 0.075 to 0.1 mm; Preferably, the fine scale expanded graphite is oxidized and acidified by potassium permanganate, perchloric acid, glacial acetic acid and nitric acid. 细鳞片石墨 ∶m 高锰酸钾 :V 高氯酸 :V 冰乙酸 :V 硝酸 =5g:1.7g:10mL:3.5mL:3mL, the reaction environment temperature is 40°C, the reaction time is 30min, and then the fine flake expanded graphite is obtained at a high temperature of 600°C, and the expansion volume of the fine flake expanded graphite is 190mL / g.
3. The internal waterproof material for autoclaved aerated concrete according to claim 1, characterized in that: The aerated concrete waste is one or more of sand aerated concrete waste, fly ash aerated concrete waste, and slag aerated concrete waste; Preferably, the aerated concrete waste is of the same type as autoclaved aerated concrete.
4. The internal waterproof material for autoclaved aerated concrete according to claim 1, characterized in that: The water content of the aerated concrete waste is not higher than 2wt%; the aerated concrete waste is obtained by crushing aerated concrete blocks, and the particle size of the aerated concrete waste is 1-5mm.
5. The internal waterproof material for autoclaved aerated concrete according to claim 1, characterized in that: The carbon content of the earthy graphite is ≥95wt% and the particle size is 0-0.045μm.
6. The internal waterproof material for autoclaved aerated concrete according to claim 1, characterized in that: The modified light calcium carbonate is prepared by modifying calcium carbonate, and the specific operation is as follows: light calcium carbonate and calcium stearate are weighed in a mass ratio of 1:0.015 and mixed evenly, and then ground by a vibration mill for 2 to 5 minutes to obtain the modified light calcium carbonate.
7. The internal waterproof material for autoclaved aerated concrete according to claim 1, characterized in that: The CaO content of the quicklime is ≥80wt% and the particle size is 10-30mm.
8. The internal waterproof material for autoclaved aerated concrete according to claim 1, characterized in that: The silicon ash is a byproduct of smelting ferrosilicon alloy or silicon metal in an electric arc furnace, and the SiO2 content is ≥90wt%.
9. The internal waterproof material for autoclaved aerated concrete according to claim 1, characterized in that: The dispersant is a cement grinding aid.
10. The method for preparing an internally-added waterproof material for autoclaved aerated concrete according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Weigh fine flake expanded graphite, earthy graphite and aerated concrete waste according to mass ratio, grind and mix them evenly to obtain mixture A; S2. Weigh modified light calcium carbonate, quicklime and silica fume according to the mass ratio, grind and mix them evenly to obtain a mixture B; S3. Weigh mixture A and mixture B in a mass ratio of 1:4, add a dispersant in an amount less than 0.5wt% of the total mass of mixture A and mixture B, grind and mix until the residue on a 45μm sieve is ≤8%, and obtain an internally mixed waterproof material.
Citation Information
Patent Citations
Autoclaved aerated concrete block or plate and preparation method thereof
CN105036677A
Aerated concrete manufactured by stone material waste and manufacturing method thereof
CN105110811A
Cement concrete inner-doping waterproof agent and preparing method thereof
CN105693135A
Preparing method of nano-modified high permeability resistant concrete
CN107032734A
Coal-ash-doped graphene oxide concrete and preparation method thereof
CN108117335A